Propuesta de Metodología para la Administración de Proyectos de Incremento de la Capacidad en la Infraestructura de Telecomunicaciones de la Empresa Cable Pacayas - Montenegro-Solís, Fabián Ricardo (Instituto Tecnológico de Costa Rica, 2016)
“Cable Pacayas” is an internet service provider company which offers internet and community antenna television (CATV) in Cartago. His problem is non-compliance with triple constraint (scope, time and cost) in projects to increase capacity in telecommunications infrastructure. This document presents a project management methodology to increase the chances to accomplishment with triple constraint in projects of increase capacity in telecommunications infrastructure. To develop the methodology, a diagnostic was performed to determine the current situation and gaps in project management. It is concluded that the company is small and manage simple projects. A base model for small and medium-sized enterprises (SMEs) called “6Ps” was designed, the model has principles, policies, authority, processes, procedures and templates. The proposal for project management methodology was developed using the 6Ps model, the context of telecommunications in Costa Rica, the current situation of “Cable Pacayas” and the list of gaps of “Cable Pacayas”.
Proyecto de graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica, Área académica de Gerencia de Proyectos, 2016
Keywords: Elaboración de proyectos; Gerencia; Pequeña y mediana empresa; Telecomunicaciones; Cable Pacayas